2010
DOI: 10.1111/j.1742-1241.2010.02353.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of treatment with sitagliptin or glipizide in patients with type 2 diabetes inadequately controlled on metformin: a 2-year study

Abstract: In patients with type 2 diabetes, adding sitagliptin to metformin monotherapy improved glycaemic control over 2 years, similar to the glucose-lowering efficacy observed with adding glipizide, but with greater durability and generally better maintenance of beta-cell function. Sitagliptin was generally well tolerated with a lower risk of hypoglycaemia and weight loss compared with weight gain observed with glipizide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
134
1
9

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(154 citation statements)
references
References 22 publications
10
134
1
9
Order By: Relevance
“…1). In the two longest-running trials, the 'escape phenomenon', assessed by a secondary increase in HbA 1c levels between weeks 24 and 104 following a good initial HbA 1c reduction, was significantly less pronounced with sitagliptin 100 mg or vildagliptin 100 mg than with glipizide or glimepiride, respectively [28,31], suggesting better β-cell protection and durability of glucose control with a DPP-4 inhibitor.…”
Section: Gliptins Combined With Metforminmentioning
confidence: 99%
See 1 more Smart Citation
“…1). In the two longest-running trials, the 'escape phenomenon', assessed by a secondary increase in HbA 1c levels between weeks 24 and 104 following a good initial HbA 1c reduction, was significantly less pronounced with sitagliptin 100 mg or vildagliptin 100 mg than with glipizide or glimepiride, respectively [28,31], suggesting better β-cell protection and durability of glucose control with a DPP-4 inhibitor.…”
Section: Gliptins Combined With Metforminmentioning
confidence: 99%
“…However, in the present review, only head-to-head trials vs active comparators are presented in brief. Gliptins have also been compared with SUs (glimepiride, glipizide, gliclazide) [27][28][29][30][31][32][33][34], TZDs (pioglitazone 30 mg, rosiglitazone 8 mg) [35][36][37][38][39] and GLP-1 receptor agonists (exenatide, liraglutide) [36,40,41]. However, only one head-to-head study compared two different DPP-4 inhibitors in the same trial: saxagliptin 5 mg with sitaglitptin 100 mg as add-ons to basal metformin therapy [42].…”
Section: Gliptins Combined With Metforminmentioning
confidence: 99%
“…However, the evidence supporting this proposed benefit is limited. 46 In fact, a recent randomized controlled trial 46 suggested that dipeptidyl peptidase-4 inhibitors do not confer benefits in terms of sustained glycemic control. Nevertheless, if future long-term studies demonstrate differences in glycemic durability between agents over time, or in other clinically important outcomes, cost-effectiveness estimates will have to be updated.…”
Section: Limitationsmentioning
confidence: 99%
“…Yanai et al [3] had found a significant and negative correlation between change in body Another study performed by Seck et al [4] result was for the PP cohort, Relative to baseline, sitagliptin was associated with significant weight loss (p<0.05) (-1.6 kg) compared with weight gain (+0.7 kg) with glipizide. Study conducted by Yang et al [5] in 2012 revealed a small decrease from baseline body weight in the placebo group compared with no change in the sitagliptin group (between-group difference 0.5kg; p<0.01).…”
Section: Methodsmentioning
confidence: 96%